Internalisasi Karakter melalui Model Project Citizen pada Pembelajaran Pendidikan Pancasila dan Kewarganegaraan - Dharma, Surya; Siregar, Rosnah (JUPIIS: Jurnal Pendidikan Ilmu-ilmu Sosial, 2014)
This writing deals with developing moral values by the âproject citizenâ through several stages of its learning. Hopefully this article could act its role in enlightening and motivating for the teachers to be able to use this model later. Starting from the idea of character building by John Dewey (1859-1952) through the flow of Progressivism. He explains that "schools should make students as citizens to be more democratic, free thinking and intelligent". It can be interpreted that the role of the school as an institution must provide learning that can develop a wide range of student competence. The most appropriate learning strategies to achieve what is thought of this school is by using learning model of âproject citizenâ. This model is basically based on the strategy of inquiry learning, discovery learning, problem solving, and research-oriented learning. From the experiments which conducted, using the model is able to achieve competency in the subject of Civic Education. The model of project citizen learning has become the best model, which is able to develop the character of students through the process of participative learning. Therefore, educating character as a pillar of our national education goals, could be developed through the learning model of project citizen.